Spatial epidemiology of cancer : data types, spatial aggregation and geographical patterns at mainland Portugal - Silva, Rita da Mata Graça Roquette e (2018)
A thesis submitted in partial fulfillment of the requirements for the degree of Doctor in Information Management Specialization in Geographical Information Systems